Breakaway Americas the unmanifest future of the Jacksonian United States - Richards, Thomas Jr. 1983- (Johns Hopkins University Press, 2020)
"The author examines six attempts by groups of nineteenth-century Americans to escape, rather than extend, the borders of the United States. Although their goals and methods varied, these six groups -- 'patriots' who attempted to overthrow British rule in Canada, post-removal Cherokees in the Indian Territory, Mormons in the Salt Lake Valley, Anglo-American overland immigrants in both Mexican California and Oregon, and Anglo-Americans in Texas -- had a common mind-set: they were not expansionists and did not believe in manifest destiny. They hoped instead to form new, independent republics based on the 'American values' that they felt were no longer being upheld in the United States"--
"Published in cooperation with the William P. Clements Center for Southwest Studies, Southern Methodist University."
Keywords: Geschichte 1835-1845; Republikanismus; Autonomiebewegung; Nordamerika; Separatist movements / History / 19th century; United States / History / Autonomy and independence movements; United States / History / 19th century; United States / Politics and government / 19th century; Autonomy and independence movements; Politics and government; Separatist movements; United States; 1800-1899; History; Hochschulschrift